Identification of PANoptosis-related genes as biomarkers in ischemic stroke - Jiang, Anna; Zhang, Hongjing; Jia, Xinglei; Zhao, Huangying; Zhao, Hong; Lu, Zhengyu (Frontiers in Neurology, 2025)
IntroductionPANoptosis (panoptotic cell death) is an inflammatory, lytic cell death pathway driven by caspases and RIPKs and regulated by PANoptosome complexes, distinguishing it from other cell death pathways. There is a close potential link between PANoptosis and neuroinflammation, with both regulating each other through complex molecular mechanisms and jointly participating in the pathological processes of neurological diseases.MethodsTo investigate whether PANoptosis exists in IS and identify the master regulators of PANoptosis and their relationship. Gene microarray data were downloaded from the Gene Expression Omnibus (GEO) and differentially expressed genes (DEGs) were identified using R software. R software and Cytoscape were used to analyze and visualize the data. Gene ontology-biological process and the Kyoto Encyclopedia of Genes and Genomes were used to analyze the biological processes and possible pathways. The LASSO regression analysis, Random Forest (RF) and support vector machine (SVM) methods were used to identify key genes for diagnostic model construction. In addition, biomarkers with higher diagnostic values for ischemic stroke were validated using other GEO datasets.Results and discussionFinally, 4,392 upregulated genes and 4,356 downregulated genes were identified in the peripheral blood of 23 normal controls and 69 patients with IS from the GSE58294 dataset. Crossing the differential genes with 277 PANoptosis genes yielded 60 upregulated genes and 58 downregulated genes. The top 10 hub upregulated genes and hub downregulated genes were identified using Cytoscape. Through LASSO regression, RF and SVM, four intersecting genes were screened from upregulated genes, and six intersecting genes were screened from downregulated intersecting genes. These ten intersecting genes were differentially expressed in the validation GSE16561 dataset. The results identify upregulated genes (CASP1, CTNNB1, CASP8) and downregulated genes (PSMC3) as key regulators of PANoptosis in IS. These findings demonstrate that PANoptosis-related genes are differentially expressed in IS and may serve as potential biomarkers.